Examination of geometric accuracy of the agricultural monitoring system by landscape-oriented remote sensing methods - Molnár, Dániel (JOURNAL OF LANDSCAPE ECOLOGY, 2019)
The most dominant actors in the European landscape are the legitimate users of agricultural areas. They can either receive area-based payments based on the cultivated plants or on the uncultivated land kept in condition eligible for support, in line with the provisions of community and national legislation. Furthermore, land-based payments can be received via other rural development measures as well. According to the European Commission regulation the appropriate and eligible claim of the area-based subsidies shall be controlled by the member states. The Control with Remote Sensing (CwRS), which has been promoted by the Directorate-General for Agriculture and Rural Development (DG AGRI) since 1993 and has been delegated to the Joint Research Centre (JRC) in 1998, is the most robust remote sensing technique. Remote sensing based on high resolution (
Keywords: CAP 2020; technical tolerance; Sentinel; monitoring; LPIS; CwRS